Emotion Regulation in Pediatric Obsessive-Compulsive Disorder and Related Interventions: A Scoping Review - Shivali Sarawgi; Rachel E. Mathews (Children)
Background/Objectives: Maladaptive emotion regulation (ER) and emotion dysregulation (ED) have long been associated with obsessive-compulsive disorder (OCD) as etiological and maintaining factors. Despite building interest in the field along with ancillary research into “rage OCD” (likely an example of ED), targeting the relationship between OCD and ER/ED has been understudied in pediatric OCD populations. The aim of this review was to elucidate the current state of the literature regarding ER/ED, its relationship to pediatric OCD, and related interventions. Methods: A scoping review examined how ER/ED are related to OCD, particularly in pediatric populations, and the efficacy of interventions to affect ER/ED for youth, with a focus on youth diagnosed with OCD. Results: A total of 182 publications were reviewed. While not always consistent, a majority of studies found a significant relationship between measures of ER or ED and OCD broadly, as well as with specific OCD symptom dimensions. A number of previously existing interventions, adaptations of those interventions, and newly presented interventions were found to affect ER/ED in youth; however, few studies have effectively targeted ER/ED for pediatric OCD, specifically. As such, the mechanism of change is not well understood. Conclusions: Findings from this review suggest that the increasing focus on ER/ED in pediatric OCD is warranted and in need of continued research. ER/ED can be effectively changed by interventions in youth, but the role ER/ED-change plays in pediatric OCD symptom improvement remains unclear. Implications for future study are examined.